RELATIONSHIP BETWEEN HUMAN RIGHTS AND NATION BUILDING – TAN SRI HASMY AGAM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 – The words ‘human rights’ and ‘nationbuilding’ may appear to be obvious and straightforward for some people, but not necessarily for others, as understandings and perspectives may differ from one individual or a group to another.